Evidências de confiabilidade e validade do instrumento de avaliação do processamento sensorial - Sensory Profile (Dunn, 1999): um estudo preliminar - Mattos, Jací Carnicelli (2018)
Considering the importance and need for studies that analyze the psychometric properties of assessment tools, this study investigated the psychometric parameters of reliability and validity of the Sensory Profile (Dunn, 1999) as translated and culturally adapted to Brazilian Portuguese. As a tracer of sensory difficulties and an indicator that something is not going well in the cerebral processing of sensory information, the instrument is a relevant tool to establish a Sensory Profile that can guide the planning and suggestion of activities related to sensory experiences. The aim was to investigate the psychometric parameters of reliability and validity of the Sensory Profile, based on the version already translated and culturally adapted to Brazilian Portuguese, conducting a descriptive, cross-sectional and correlational study. The sample was composed of 336 children aged 05 to 10, from both genders, 298 of which did not have neurodevelopmental disorders and 38 of which had Autistic Spectrum Disorder (ASD). The tool showed satisfactory internal consistency with alpha values above 0.60 in most categories and factors. The scores of the sample of Brazilian children without neurodevelopmental disorders differed from the American normative sample, and led to the establishment of score values related to the ranges of sensory performance that were different from the values for American children (typical performance, probable difference and definite difference). Children with Autism Spectrum Disorder were classified in the ranges of probable difference and/or definite difference. In this preliminary study we found evidence of reliability and validity of the Sensory Profile as translated and culturally adapted to Brazilian Portuguese through the verification of its psychometric properties.